Excess Rab4 rescues synaptic and behavioral dysfunction caused by defective HTT-Rab4 axonal transport in Huntington's disease. - White, J.A.; Krzystek, T.J.; Hoffmar-Glennon, H.; Thant, C.; Zimmerman, K.; Iacobucci, G.; Vail, J.; Thurston, L.; Rahman, S.; Gunawardena, S. (Acta neuropathologica communications, 2020)
Huntington's disease (HD) is characterized by protein inclusions and loss of striatal neurons which result from expanded CAG repeats in the poly-glutamine (polyQ) region of the huntingtin (HTT) gene. Both polyQ expansion and loss of HTT have been shown to cause axonal transport defects. While studies show that HTT is important for vesicular transport within axons, the cargo that HTT transports to/from synapses remain elusive. Here, we show that HTT is present with a class of Rab4-containing vesicles within axons in vivo. Reduction of HTT perturbs the bi-directional motility of Rab4, causing axonal and synaptic accumulations. In-vivo dual-color imaging reveal that HTT and Rab4 move together on a unique putative vesicle that may also contain synaptotagmin, synaptobrevin, and Rab11. The moving HTT-Rab4 vesicle uses kinesin-1 and dynein motors for its bi-directional movement within axons, as well as the accessory protein HIP1 (HTT-interacting protein 1). Pathogenic HTT disrupts the motility of HTT-Rab4 and results in larval locomotion defects, aberrant synaptic morphology, and decreased lifespan, which are rescued by excess Rab4. Consistent with these observations, Rab4 motility is perturbed in iNeurons derived from human Huntington's Disease (HD) patients, likely due to disrupted associations between the polyQ-HTT-Rab4 vesicle complex, accessory proteins, and molecular motors. Together, our observations suggest the existence of a putative moving HTT-Rab4 vesicle, and that the axonal motility of this vesicle is disrupted in HD causing synaptic and behavioral dysfunction. These data highlight Rab4 as a potential novel therapeutic target that could be explored for early intervention prior to neuronal loss and behavioral defects observed in HD.